2014
DOI: 10.1080/03036758.2014.972962
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and ancient DNA analyses reveal inaccurate labels on two of Buller's bird specimens

Abstract: Historical museum skins are an important genetic resource for taxonomic, phylogeographic and conservation genetic research. However, their utility can be compromised by errors in specimen labels concerning taxonomic identity, collection locality and collector. Here we use morphological comparisons and ancient DNA analysis to show that two Auckland Island Shags (Leucocarbo colensoi) in the Sir Walter Buller collection of the Canterbury Museum, New Zealand, are mislabelled. Given that Buller was able to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In the museum industry, accurate records and archiving are obviously of high priority, with labels and registers providing vital information about the specimens [ 40 , 41 , 42 ]; it therefore seems unexpected that the two bird skins could have been “lost”. However, at the time, their significance as the final remnants of the species was not recognised.…”
Section: Discussionmentioning
confidence: 99%
“…In the museum industry, accurate records and archiving are obviously of high priority, with labels and registers providing vital information about the specimens [ 40 , 41 , 42 ]; it therefore seems unexpected that the two bird skins could have been “lost”. However, at the time, their significance as the final remnants of the species was not recognised.…”
Section: Discussionmentioning
confidence: 99%
“…These studies are valuable because museum collections, their field records, and historical demographic data can test theory and develop methodology that can be applied to older, more-degraded archaeological samples. When utilizing both museum and archaeological collections, care must be taken to ensure that samples are properly identified and labeled [75,76], but ancient DNA from the host, in addition to a pathogen, can be useful in detecting cryptic species and misidentifications.…”
Section: Ancient Disease Ecologymentioning
confidence: 99%
“…Advances in DNA extraction techniques and sequencing technologies have facilitated the use of historical museum specimens in conservation genetic studies (Wandeler et al, 2007). Retrieval of ancient DNA (aDNA) from such specimens can be used to examine temporal changes in genetic diversity (Thomas et al, 1990), test for congruence between collection locality and genetic data (Boessenkool et al, 2009), determine the provenance of specimens for which locality data are lacking (Shepherd et al, 2013), and assign mislabeled specimens to the correct taxonomic unit (Rawlence et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, Travers was probably falsely credited with the discovery of South Island snipe, as it is likely that he never visited the type locality of C. iredalei and that the type specimens were sourced from an unknown collector by H. H. Travers, before being sold to Lord Rothschild (Miskelly, 2012). Finally, it has also been suggested that Sir Walter Buller, who sold avian specimens to Rothschild (Bartle and Tennyson, 2009), mislabeled parts of his personal collection upon sale, with the misidentification of two Auckland Island shags (Leucocarbo colensoi) attributed to poor record keeping (Rawlence et al, 2014a). NHMUK 1939.12.9.75 could potentially have been supplied to Rothschild by a dealer such as Travers or Buller.…”
Section: Introductionmentioning
confidence: 99%